Exploring Citizen’s Satisfaction with the Infrastructure of Services at a Local Seaport in Ternate, North Maluku - Johan Fahri (Journal of Indonesian Economy and Business, 2022)
Main objective: This research aims to explore the aspects of citizen satisfaction with basic government infrastructures, using a specific seaport as the site for the research. Background problems: Their impacts of on people’s lives of basic infrastructures that the Indonesian government is currently developing should be measured, particularly how satisfied citizens are with these infrastructures. Extant literature indicates there has been limited discussion using qualitative research—which has mainly used the grounded theory approach—to understand citizen satisfaction. This context has rarely been used to explore users’ satisfaction with the local seaport. Novelty: This current research offers theoretically grounded and real aspects of citizen satisfaction that lead to a testable model to enrich a comprehensive conversation of customer satisfaction in the public sector. Methods: This research has used a grounded theory approach to define and explore, in depth, the main aspects of satisfaction felt by citizens who are the customers frequently using the seaport to enable their mobility between the islands. Results: The results identify five main aspects of citizen satisfaction when using local seaports. These aspects were used to revisit the dimensions of SERVQUAL. The sentiments of the users were also recognized and analyzed as a part of an overall evaluation of the satisfaction. Conclusion: While previous studies have provided a great deal of evidence on citizen satisfaction, the results of this study are drawn from an in-depth examination of those earlier pieces of evidence, including those regarding emotions and sentiments. Future studies are also recommended to overcome some of the limitations of this research.